Joint-stock companies: between establishment and dissolution (The International Journal for Scientific Research, 2026)
This study examined joint-stock companies from their inception to their dissolution. The study aimed to explain the concept of this type of company by mentioning its definition, characteristics, and types. It also addressed its legal nature, the tension between the idea of a contract and that of an organization. Then, in its first section, it explained how to establish joint-stock companies by outlining how to draft articles of association, how to subscribe to them, and how to acquire legal personality. In the second section, the study detailed how to dissolve this type of company.
Keywords: Law; Commercial Companies; Joint Stock Companies; Saudi Commercial System